Bird collisions with power lines: Prioritizing species and areas by estimating potential population‐level impacts. Issue 6 (12th February 2019) - D'Amico, Marcello; Martins, Ricardo C.; Álvarez‐Martínez, Jose M.; Porto, Miguel; Barrientos, Rafael; Moreira, Francisco
Abstract: Aim: Power lines can represent an important source of bird mortality through collision. The identification of more susceptible species, in terms of expected population‐level impacts, requires detailed biological and mortality information that is often difficult to obtain. Here, we propose a species prioritization method based on relatively easily accessed information, aimed to identify both species and areas with the potentially highest extinction risk due to collision with power lines. Location: As a case study, we applied this method to the communities of resident breeding birds of Spain and Portugal. Methods: For each considered species, the method takes into account the morpho‐behavioural susceptibility to collision with power lines, the susceptibility to extinction and the spatial exposure to collision with power lines. Results: Our method highlighted that the most susceptible species were large, long‐lived and slow‐reproducing birds, often habitat specialists with hazardous behavioural traits (especially flight height and flocking flight), with high spatial exposure to collision risk with power lines and unfavourable conservation status. Based on the distribution ranges of these species, we produced a map of hotspots for extinction risk due to collision of such priority species for each country. These areas should be considered a priority for the implementation of mitigation measures including route planning and wire marking. Main conclusions: Overall, the proposed method can be applied to any bird community in any geographic area of the world where information on power‐line distribution and published information on species traits, distribution and conservation status is available, generating valuable lists of both priority species and areas in which collision risk with power lines can potentially produce local or even global extinctions.